Oil spill detection using sentinel 1 SAR data at Cyprus’s coasts - Melillos, George; Hadjimitsis, Diofantos G. (My University, 2021)
Remote sensing is considered as an increasingly important technology for Maritime ecosystem. The aim of this paper is to show how to detect and map oil spills in the Cyprus Region using freely available Sentinel 1 SAR imagery data. Oil spill is automatically detected using Oil Spill detection tool of Sentinel Application Platform (SNAP). The methodology is applied on several satellite images to identify the effects of oil spill compared to the clean sea conditions. The comparison was made using two different polarization; vertical polarization (VV) and horizontal comparison (VH). The preliminary results shows that the Sentinel-1 SAR data would give effective results and spatial information on oil spill detection to decision-makers.